Death in Avignon : a Penelope Kite novel - Kent, Serena (Harper, 2020)
"The second book in the Penelope Kite series. After an eventful first few months in Provence, it seems Penelope is finally settling into her delightful new life, complete with a gorgeous love interest in the mayor of St. Merlot. When Penelope and the mayor Laurent Millais attend a glamorous gallery opening, a scandal-free evening is not in the cards. The evening comes to a horrifying halt when a controversial painter, Poland Doncaster, chokes to death. A tragic accident? Or a malicious plot? Embroiled once more in a murder investigation, Penelope discovers that any number of jealous lovers and scheming rivals could be involved. And with dashing art dealers to charm, patisseries to resist, and her own friends under suspicion, Penelope will need all her sleuthing talents to uncover the truth"--